Fast and efficient processes for oxidation and monitoring of polycyclic aromatic hydrocarbons in environmental matrices - Araújo, Kelvin C.; Nóbrega, Eryka T.D.; Moreira, Ailton J. [UNESP]; Lemos, Sherlan G.; Fragoso, Wallace D.; Pereira, Ernesto C. (Elsevier, 2024)
This study proposes a new approach for the efficient photodegradation of polycyclic aromatic hydrocarbons (PAH) and derivatives. PAH removal was achieved in just a few minutes using a microwave photochemical reactor capable of producing a high concentration of •OH (2.3 mmol L−1 h−1). Fluorescence excitation-emission matrix (EEM) spectroscopy coupled to parallel factor analysis (PARAFAC) was used for quantifying two PAH and one alkylated PAH at low concentrations (μg L−1). These results highlight the high potential of the photochemical degradation system coupled to EEM-PARAFAC as an alternative fast, inexpensive, and efficient approach for environmental remediation studies of PAH.
Keywords: Advanced oxidation processes; Emerging pollutants; Fluorescence excitation-emission matrix; PARAFAC; Polyaromatic hydrocarbons